Big Players Out of Synch : Spillovers Implications of US and Euro Area Shocks - Osorio Buitron, Carolina (IMF Working Papers; Working Paper ;, 2015)
Given the prospects of asynchronous monetary conditions in the United States and the euro area, this paper analyzes spillovers among these two economies, as well as the implications of asynchronicity for spillovers to other advanced economies and emerging markets. Through a structural vector autoregression analysis, country-specific shocks to economic activity and monetary conditions since the early 1990s are identified, and are used to draw implications about spillovers. The empirical findings suggest that real and monetary conditions in the United States and the euro area have oftentimes been asynchronous. The results also point to significant spillovers among them, in particular since early 2014-with spillovers from the euro area to the United States being particularly large. Against the backdrop of asynchronous conditions in these two economies, spillovers from real and money shocks to emerging markets and non-systemic advanced economies could be dampened.